2022
DOI: 10.1097/acm.0000000000004743
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Resident Race and Ethnicity and Clinical Performance Assessment Scores in Graduate Medical Education

Abstract: PurposeTo assess the association between internal medicine (IM) residents' race/ ethnicity and clinical performance assessments. MethodThe authors conducted a cross-sectional analysis of clinical performance assessment scores at 6 U.S. IM residency programs from 2016 to 2017. Residents underrepresented in medicine (URiM) were identified using self-reported race/ ethnicity. Standardized scores were calculated for Accreditation Council for Graduate Medical Education core competencies. Cross-classified mixed-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…These results build on prior evidence showing differences in IM performance evaluations between URiM and non-URiM residents at 6 residency programs. 17 Our findings advance this work by demonstrating racial inequities in Milestone assessments for all trainees from racial and ethnic groups that have been historically marginalized in medicine, including Asian residents. In addition, our study furthers this research by examining assessments in a sample of more than 9000 trainees from 2 successive cohorts of IM residents.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These results build on prior evidence showing differences in IM performance evaluations between URiM and non-URiM residents at 6 residency programs. 17 Our findings advance this work by demonstrating racial inequities in Milestone assessments for all trainees from racial and ethnic groups that have been historically marginalized in medicine, including Asian residents. In addition, our study furthers this research by examining assessments in a sample of more than 9000 trainees from 2 successive cohorts of IM residents.…”
Section: Discussionsupporting
confidence: 72%
“…The Milestone system was designed to support formative assessment, bolster professional development, and enhance the quality of assessments. 15,16 However, a recent study 17 of ACGME's Milestone assessment system reported differences in assessment by race and ethnicity, suggesting that the Milestone assessment system may be vulnerable to bias. This study 17 was limited in cohort size and the number of included GME training sites; therefore, it is unclear whether these findings are generalizable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, men faculty rated racially minoritized residents 0.13 points lower than White residents in professionalism competencies. 23 These findings highlight the unconscious imbuement of racialized and gendered standards in assessment of professionalism.…”
Section: Professionalism As Policingmentioning
confidence: 99%
“…In letters of recommendation, URM applicants are more likely to be described using grindstone words to highlight effort as compared with White applicants who are more likely to be described with standout descriptors that highlight achievement . A hidden curriculum prevails, in which certain characteristics of racial and ethnic or cultural identity, such as dress, hair, and speech, are seen as examples of unprofessional behavior because they do not conform to the broader and historic norms . These inequitable metrics and biases serve to disadvantage or exclude already historically marginalized groups.…”
Section: Racial and Ethnic Underrepresentation Among Dermatologistsmentioning
confidence: 99%